Kehancuran Alam Semesta dalam Al-Qur'an Perspektif Kosmologi - Amalia, Efa Ida (SUHUF, 2009)
The purpose of this research is to know about the process and the steps of the destruction of the Universe (kiamat) in the Qur'an. This phenomenon will be explained through cosmological perspective. Al-Qur'an mentions the phenomenon of the end of the world (universe) or (kiamat) in many verses for more than 700 times. Therefore, human beings are supposed to be able to Ã¢â‚¬Å“readÃ¢â‚¬Â the phenomenon of the universe. According to the Qur'an, destruction is divided into two categories: the first is total destruction of the universe and the second is the day of resurrection. The first one is the final destruction of the universe known as the doomsday. At this stage, the expansion of the universe is ceased and leaves the contraction space caused by gravitation. As theÃ‚ result, all things are more closed to others and destruction cannot be avoided. The second destruction is the destruction of the earth which is caused by human beings attitude